A multifunctional metal-biopolymer coordinated double network hydrogel combined with multi-stimulus responsiveness, self-healing, shape memory and antibacterial properties. (6th May 2020) - Yan, Kun; Xu, Feiyang; Wang, Chunyu; Li, Yingying; Chen, Yuanli; Li, Xiufang; Lu, Zhentan; Wang, Dong
Abstract : A universal, straightforward macroscale assembly technology has been presented for fabrication of polysaccharide-based multifunctional DN gels based on metal coordination chemistry. Abstract : Outfitted with abundant hydrogen bonding and coordination active groups, carboxymethyl chitosan (CMC) possesses a class of naturally occurring ligands for coordination with metal ions, establishing its excellent potential for various fields. Herein, by incorporating the naturally derived CMC into a thermally reconfigurable agarose (Agar) gel medium, a novel type of metal-biopolymer coordinated double network hydrogel (DN gel) was successfully fabricated via the strong coordination interactions. The interpenetrated CMC was confirmed to retain its excellent chelating abilities within the bulk gel matrix, which resulted in a series of metal-coordinated DN gels through spontaneous self-associative complexation with metal ions such as Cu 2+, Zn 2+, Ni 2+, Co 2+, Fe 3+, and Cr 3+ . Moreover, these two types of physical cross-links are functionally independent and reversible, which enables the programming of the hydrogel with multi-functionality, including pH-regulated shape memory behavior, multi-staged self-healing properties and durable antibacterial activities. Thus, we believe that the successful preparation of such a coordination-driven DN gel will lead to the development of biopolymer-based multifunctional hydrogels, as well as provide new insight into nanocomponent assembly and soft electronic biosensing systems for biomedical applications.